Assembly line design with tools vibration. Issue 13 (2019) - Finco, Serena; Abdous, Mohammed-Amine; Battini, Daria; Calzavara, Martina; Delorme, Xavier
Abstract: This study integrates vibrations aspects in the Assembly Line Design Problem (ALDP). During the last decade, ergonomic aspects have been considered by several points of view in the assembly design problems in order to reduce work-related musculoskeletal disorders. However, the workers vibration exposure level, caused by the use of automatic tools to perform some tasks, has not still discussed as a part of ALDP. For this reason, a new model is here proposed to compare the total costs of an assembly line with and without the integration of the ISO 5349-1, the European norm that defines the vibration exposure limit for workers. The application of the model here proposed in two real industrial contexts shows the effects of the vibration level maximum exposure in the final assembly line design costs.